PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF ANALYTICAL THINKING IN ADOLESCENTS (Proceedings of International Educators Conference, 2024)
This article explores in theory the pedagogical-psychological foundations of the development of analytical thinking in adolescents, the importance of analytical thinking in improving the effectiveness of the educational process. In addition, through analytical thinking, the process of finding solutions to problems, evaluating results and making decisions has been scientifically analyzed.